REPLACING ENDORSERS WITH ARTIFICIAL INTELLIGENCE: INNOVATION IN THE ADVERTISING WORLD - Azad Sristy, Sadia Binte; Musanna, Noor (PEOPLE: International Journal of Social Sciences, 2024)
At one time, we thought that artificial intelligence was just fantasy. However, we did not imagine that this dream would become a reality in the 21st century and would have such an impact on our day-to-day lives. Nowadays, AI has made many difficult tasks in our daily lives easier, and work time has also decreased. Currently, Artificial Intelligence is being used in various sectors. But, after witnessing the capability, it is clear that AI will revolutionize the business world. Advertising is a significant part of the business sector. AI is expected to emerge as a game changer, especially in advertising. New entrepreneurs can market and advertise their products at relatively low cost. With AI, they can hire prominent endorser’s "personality" to advertise at a reasonable cost, which is currently out of imagination for new entrepreneurs. AI is going to emerge as a generational advancement for the business and advertising world around the globe. If advertisers develop an AI that can learn the personality of an individual and can ethically use the character to create ads or a live video, the expense of marketing will significantly decline. Statistical tools will be used to analyze the quantitative data, and thematic examination will be applied to dissect the qualitative data. Try to fill the gap and overcome the problem using primary and secondary data. Find the best ways to reduce the risk factors and expand economic growth.